A modelling approach for railway overhead line equipment asset management - Kilsby, Paul; Remenyte-Prescott, Rasa; Andrews, John (Elsevier, 2017)
The Overhead Line Equipment (OLE) is a critical sub-system of the 25kV AC overhead railway electrification system. If OLE asset management strategies can be evaluated using a whole lifecycle cost analysis that considers degradation processes and maintenance activities of the OLE components, the investment required to deliver the level of performance desired by railway customers and regulators can be based on evidence from the analysis results. A High Level Petri Net (HLPN) model, proposed in this paper, is used to simulate the degradation, failure, inspection and maintenance of the main OLE components and to calculate various statistics, associated with the cost and reliability of the system over its lifecycle. The HLPN considers all the main OLE components in a single model and it can simulate fixed frequency inspections and condition-based maintenance regimes. In order to allow the relevant processes to be modelled accurately and efficiently, the HLPN features are used, such as specific data about individual components is taken account of in the general model. The HLPN, developed using international standards, is described in detail and a framework of its analysis for reliability and lifecycle cost evaluation is proposed. In this novel whole system model different OLE component types and their instances on a line are modelled simultaneously, and the dependencies are considered in terms of opportunistic inspection and maintenance. An example HLPN for the catenary wire is used to illustrate the model, and an application of the methodology for whole lifecycle cost evaluation of a two-mile OLE line is presented.